BENTUK PENYAJIAN TARI NGUNDANG KARYA RADEN GUNAWAN DI KABUPATEN BANYUASIN: Tari Ngundang - Apriyani, Anisa; Adoma, Auzy Madona; Rochayati, Rully (Universitas Negeri Surabaya, 2025)
Ngundang Dance is a creative dance created by Raden Gunawan in 2002, raised from a hereditary tradition carried out by the people of Banyuasin regency. The Ngundang dance tells about the habits of the Banyuasin people in gathering relatives and friends to attend and help with celebrations or almsgiving. The purpose of the writing is to describe the form of presentation of the Ngundang dance by Raden Gunawan in Banyuasin Regency. The research method used is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The form of presentation can make the dance work presented well organized, so that it can be studied and analyzed as a whole or divided according to the elements needed. The results of the research are in the form of a description of the form of presentation based on the theory of Y. Sumandiyo Hadi which consists of various elements such as dance movements, floor patterns, accompaniment, makeup, dress, dancers, and performance venues.